POTENTIAL FOR FRAUD IN THE MANAGEMENT OF JKN FUNDS AT COMMUNITY HEALTH CENTERS (Case study at Community Health Centers in “Hastinapura” District) - Himmayatul W; Mohammad Nizarul Alim; Prasetyono Prasetyono (Asia Pacific Fraud Journal, 2018)
The purpose of this study is to assess the potential for fraud in the management of the National Health Insurance (Indonesian: Jaminan Kesehatan Nasional /JKN) funds at Community Health Center. The research is conducted using qualitative method with case study design in Hastinapura District. The methods of data collection used are documentation, unstructured interviews and observations, which are then analyzed based on interpretation recorded by researchers. The informants consisted of 2 treasurers of JKN Health Center, 1 member of JKN team of Health Department, and 1 medicine manager of Health Center. The results of this research show that the potential for fraud in JKN funds at Health Center includes: the utilization of capitation fund which is not in accordance with the provisions of legislation, the division of service is potential for moral hazard, the operational cost of the Health Centers is colored by the entrusted activities from health department, and the excessive medicine stocks in remote Health Centers. The additional cost occurs because the Health Center is running out of medicine stock so that the patient has to increase the cost for the purchase of the medicine. The potential for fraud in non-capitation funds is that participants have to pay for actual family planning services that actually can be claimed, due to the prolonged disbursement process.